2001
DOI: 10.1016/s0896-6273(01)00433-0
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the PI-3 Kinase Signaling Pathway in Fear Conditioning and Synaptic Plasticity in the Amygdala

Abstract: Western blot analysis of neuronal tissues taken from fear-conditioned rats showed a selective activation of phosphatidylinositol 3-kinase (PI-3 kinase) in the amygdala. PI-3 kinase was also activated in response to long-term potentiation (LTP)-inducing tetanic stimulation. PI-3 kinase inhibitors blocked tetanus-induced LTP as well as PI-3 kinase activation. In parallel, these inhibitors interfered with long-term fear memory while leaving short-term memory intact. Tetanus and forskolin-induced activation of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
236
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(254 citation statements)
references
References 47 publications
17
236
1
Order By: Relevance
“…PI3K has been implicated in the acquisition of long-term fear memory. 290,291 Studies employing measurement of pAkt levels within the BLA following extinction training have produced very inconsistent results. Cannich et al 288 reported no significant increase in pAkt in the BLA of extinguished wild-type or cannabinoid receptor knockout (CB1À/À) mice relative to nonextinguished controls, although the ratio of pAkt levels in extinguished vs nonextinguished animals was significantly greater in the knockouts (which exhibit a profound extinction impairment) than in the wild types.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…PI3K has been implicated in the acquisition of long-term fear memory. 290,291 Studies employing measurement of pAkt levels within the BLA following extinction training have produced very inconsistent results. Cannich et al 288 reported no significant increase in pAkt in the BLA of extinguished wild-type or cannabinoid receptor knockout (CB1À/À) mice relative to nonextinguished controls, although the ratio of pAkt levels in extinguished vs nonextinguished animals was significantly greater in the knockouts (which exhibit a profound extinction impairment) than in the wild types.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…It is also possible that lowering insulin/IGF signaling ''sensitizes'' the organism to signals that transiently activate PI3K signaling. The capacity to retain transient waves of insulin/IGF/PI3K signaling activity (leading to FoxO activity oscillations) may be needed during memory retention and retrieval (Lin et al 2001;Opazo et al 2003;Chen et al 2005;Horwood et al 2006). Indeed, recent studies have also shown that injection of an IGF family member, IGF2, into the hippocampus after training enhanced memory (Chen et al 2011) and that injection of IGF2 after extinction trials facilitated extinction of memory (Agis-Balboa et al 2011).…”
Section: The Paradoxical Roles Of the Insulin/igf Signaling Pathway Imentioning
confidence: 99%
“…AKT1, although ubiquitous, is highly expressed in brain, hence critically involved in neuronal survival, but also important for neuronal excitability and synaptic plasticity by directly regulating GABA-A receptor mediated synaptic inhibition (9). It appears to be involved in neurodevelopment and working memory formation, domains potentially impaired in schizophrenia (10,11).…”
Section: Introductionmentioning
confidence: 99%